Safety evaluation of multiple horizontal curves using statistical models. (22nd June 2021) - Joseph, Neena M.; Harikrishna, M.; Anjaneyulu, M.V.L.R.
Road safety is an important aspect of road transportation. Safety evaluation of highways helps engineers in prioritising them for safety improvement and for evaluating the effectiveness of the improvement measures. Crash prediction models are very useful for evaluating the safety levels of highway elements. Many studies reported the effect of geometry and traffic factors on safety at simple (single) horizontal curves. But the situation becomes more complex when multiple horizontal curves occur. The Highway Safety Manual also does not provide a safety performance function on multiple horizontal curves. Hence, this study aims to quantify the influence of geometric characteristics of the preceding curve on crashes and develop models for evaluation of the safety performance of multiple horizontal curves on two-lane non-urban roads. The data required for this study include crash, geometric, and traffic data from 102 multiple horizontal curves.